Economical and Accurate Protocol for Calculating Hydrogen-Bond-Acceptor Strengths - El Kerdawy, Ahmed; Tautermann, Christofer S.; Clark, Timothy; Fox, Thomas (Journal of Chemical Information and Modeling, 2013)
A series of density functional/basis set combinations and second-order Moller-Plesset calculations have been used to test their ability to reproduce the trends observed experimentally for the strengths of hydrogen-bond acceptors in order to identify computationally efficient techniques for routine use in the computational drug-design process. The effects of functionals, basis sets, counterpoise corrections, and constraints on the optimized geometries were tested and analyzed, and recommendations (M06-2X/cc-pVDZ and X3LYP/cc-pVDZ with single-point counterpoise corrections or X3LYP/aug-cc-pVDZ without counterpoise) were made for suitable moderately high-throughput techniques.